Risk Of Infection In Central Venous Catheter: Review Study To Nursing Care - Andrade, Milena da Rocha de; Silva, Hamanda Garcia; Oliveira, Beatriz Guitton Renaud Baptista; Cruz, Isabel Cristina Fonseca (Online Brazilian Journal of Nursing, 2010)
Problem: The use of central venous catheters in intensive care units has been identified as an important risk factor for infection in the bloodstream. Objective: To examine the evidence in the literature about the indications and uses of central venous catheter insertion, the risk of infection, the professional conduct in relation to safe practices related to this type of device. Methods: Narrative review, which assesses the risk of infection in central venous catheters in intensive care units; by bibliographic study in database of BVS, in the time gap from 2005 to 2010 using the keywords: infection, intensive care unit , central venous catheterization and nursing care. Results: The analysis identified 03 thematic units: 1. Complications associated with central venous catheter, which evaluates the evidence from a framework of systemic infection where vascular access is implicated as a possible source, and lists the factors that influence the onset of complications associated; 2. Adoption of the correct technique of catheter-related coverage, which recommends to use the coverage appropriate to prevent skin toxicity, and increases patient comfort and satisfaction, besides attention to time of the use and signs of inflammation, 3. Realization of safe practices for the maintenance of the catheter, involving the manipulation control and use of protocols. Conclusion: We conclude that the quality of care for patients with this device is directly related to controlling the risks of infection; where efforts, not only the nurse, but the health team will be enable the application of evidence to guide a safe clinical practice and contribute to improving the quality of health care and nursing.